2019
DOI: 10.3390/ijerph16020185
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler Technique and Adherence to Inhaled Medications among Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Vietnam

Abstract: Sub-optimal chronic obstructive pulmonary disease (COPD) management has been found largely due to patients’ medication non-adherence and incorrect inhaler technique. This study aimed to examine inhaler use technique and medication adherence among Vietnamese COPD patients as well as potential associated factors. A cross-sectional study involving 70 COPD exacerbators was conducted. Inhaler technique and adherence were evaluated by the 10-item and 12-item Test of Adherence to Inhaler (TAI). Data on the history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…However, the participants might intentionally have skipped this step, since they knew they were using placebo inhalers and therefore did not think they needed to check the dose counter. Concerning the distribution of critical steps, two of four critical errors for MDIs were related to breathing, a common mistake also found in other studies [ 29 ]. Nevertheless, no clear pattern could be seen overall.…”
Section: Discussionsupporting
confidence: 74%
“…However, the participants might intentionally have skipped this step, since they knew they were using placebo inhalers and therefore did not think they needed to check the dose counter. Concerning the distribution of critical steps, two of four critical errors for MDIs were related to breathing, a common mistake also found in other studies [ 29 ]. Nevertheless, no clear pattern could be seen overall.…”
Section: Discussionsupporting
confidence: 74%
“…The effective management of chronic constrictive pulmonary conditions lies, mainly, in the proper and timely administration of medication. However, as recently reported [2], a large proportion of patients use their inhalers incorrectly. Studies have shown that possible technique errors can have an adverse impact on clinical outcome for users of inhaler medication [3,4].…”
Section: Introductionmentioning
confidence: 79%
“…This kind of attitude appears to create a disconnect between inhaler technique theory and practice, as mastery at the time of teaching does not translate into the maintenance of correct inhaler technique over time [15]. We recognize that, for the patient, there is a range of competing factors that impact their willingness, ability, and preference to using their inhalers [16][17], but we believe they can be trained successfully to use their inhalers with effective and repeated instruction [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%